pengaruh latihan small sided games terhadap keterampilan passing siswi peserta ekstrakurikuler SMK Jaya Buana Kabupaten Tangerang - Muhamad Yuken Saukani; Rhama Nurwansyah Sumarsono; Akhmad Dimyati; Irfan Zinat Achmad (Universitas Hamzanwadi, 2026)
This study was motivated by the finding that female students participating in the futsal extracurricular program at SMK Jaya Buana in Tangerang Regency still frequently make mistakes when passing, and that the coach has not yet implemented a structured small-sided games training method. The study aims to determine the effect of small-sided games training on the passing skills of female students participating in the futsal extracurricular program at SMK Jaya Buana in Tangerang Regency. The study used a pre-experimental method with a one-group pretest-posttest design. A sample of 25 female students was selected using total sampling. The research instrument consisted of a passing skill assessment sheet covering four aspects (starting stance, execution, follow-through, and passing outcome), which had been validated through expert judgment and instrument pilot testing. The intervention consisted of 8 training sessions involving small-sided games with varying formats: 2v2, 2v2+1 neutral, 3v2, 3v3, 4v2, and 4v3. Data analysis utilized the Shapiro-Wilk test for normality and the Paired Sample T-Test for hypothesis testing at a 5% significance level. The results of the study showed an increase in the average score from 10.80 (pretest) to 13.72 (posttest), representing a 27.04% increase. The paired-sample t-test yielded a calculated t-value of 7.158 > table t-value of 2.064, with a significance level (2-tailed) of 0.000 < 0.05. There is a significant effect of small-sided games training on the improvement of the female students’ passing skills.